Pembuatan Taman TOGA di Desa Ketindan Kec. Lawang, Kab. Malang oleh Mahasiswa KKN Universitas Negeri Malang - Harientya Octavi; Yessi Ervina; Yuli Savina; Diana K. Nisa; Mitra Mustaricha; Heri Setiawan; Ika Putriani (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
This community service program aims to empower residents of Ketindan Village, Lawang District, Malang Regency, through the creation of a Family Medicinal Plant Garden (TOGA) as an effort to increase awareness of the importance of utilizing traditional medicinal plants in maintaining family health. This activity was carried out by students of the 2015 Malang State University Community Service Program (KKN) with a participatory and educational approach. The implementation method includes initial observation, socialization, TOGA cultivation training, and the construction of a demonstration garden on strategic land owned by the village. The results of the activity showed an increase in community knowledge of the benefits of medicinal plants and the emergence of community initiatives to develop TOGA independently in their yards. The TOGA Garden is not only a means of providing medicinal plants, but also a space for education and social interaction for residents. This program proves that interventions based on local potential and active community participation can encourage sustainable social change at the village level.